2017
DOI: 10.1111/pde.13074
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Homozygous Missense Mutation in HOXC13 Leads to Autosomal Recessive Pure Hair and Nail Ectodermal Dysplasia

Abstract: Pure hair and nail ectodermal dysplasia (PHNED) is a rare disorder that presents with hypotrichosis and nail dystrophy while sparing other ectodermal structures such as teeth and sweat glands. We describe a homozygous novel missense mutation in the HOXC13 gene that resulted in autosomal recessive PHNED in a Hispanic child. The mutation c.812A>G (p.Gln271Arg) is located within the DNA-binding domain of the HOXC13 gene, cosegregates within the family, and is predicted to be maximally damaging. This is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…28 A previous study has shown that the p.Q271R missense mutation in Hoxc13 gene causes the PHNED and the highly conserved coding sequence between humans and rabbits ( Figure 4A,B). 28 A previous study has shown that the p.Q271R missense mutation in Hoxc13 gene causes the PHNED and the highly conserved coding sequence between humans and rabbits ( Figure 4A,B).…”
Section: A-to-g Base Conversion At Hoxc13 To Mimic Human Phned Mutamentioning
confidence: 81%
See 2 more Smart Citations
“…28 A previous study has shown that the p.Q271R missense mutation in Hoxc13 gene causes the PHNED and the highly conserved coding sequence between humans and rabbits ( Figure 4A,B). 28 A previous study has shown that the p.Q271R missense mutation in Hoxc13 gene causes the PHNED and the highly conserved coding sequence between humans and rabbits ( Figure 4A,B).…”
Section: A-to-g Base Conversion At Hoxc13 To Mimic Human Phned Mutamentioning
confidence: 81%
“…In addition, the NG‐ABEmax exhibited average base editing frequencies from 9.30% ± 3.83% to 83.37% ± 5.78% with a similar ~6 nt editing window (Figures C‐H, S5 and Table ). These target loci with A·T to G·C conversion in Psen1 (p.M146V), Sod1 (p.I151T), Lmna‐2 (p.L530P), and Hoxc13 (p.Q271R) have been reported to cause Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS), Emery‐Dreifuss muscular dystrophy (EDMD), and Pure hair and nail ectodermal dysplasia (PHNED), respectively (Figures B, S6). These results indicate that NG‐ABEmax is efficient at relaxed NG PAMs in rabbit embryos, suggesting the great potential of this system to develop animal models for precisely mimic human genetic diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these mutations (Tyr130*, Leu119Trpfs 20, His68Glnfs*84, Ser135*, 27.6 kb deletion) are nonsense mutations. Interestingly, two missense mutations in the homeodomain of HOXC13 caused ectodermal dysplasia [ 36 , 37 ]. However, the mechanism was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To date, seven mutations had been reported in this gene causing pure hair and nail ectodermal dysplasia (PHNED), which led to complete hair loss and nail dysplasia (Table 1 ) [ 33 35 ]. Interestingly, two single nucleotide polymorphisms (SNPs) (c.812A > G and c.929A > C) in the homeodomain that belong to missense mutation caused ectodermal dysplasia [ 36 , 37 ]. However, the mechanism was still unknown.…”
Section: Introductionmentioning
confidence: 99%